Developing Speaking Test through Project Based Learning in Procedure Text Material - Sa'adah, Halimatus (Universitas Nurul Jadid, 2023)
This study focuses on the development of speaking tests through project-based learning in procedure text material. The study aims to assess students' speaking abilities by integrating project-based learning into the teaching and learning process. The research follows a research and development (R&D) method, adapting the research cycle proposed by Borg & Gall (1981) and simplifying it into eight stages: (1) Research and Information Gathering (2) Development of the Initial Product (3) Expert Validation (4) Revision (5) Product Trial (6) Revision (7) Field Trial (8) Final Product. The data were collected through a questionnaire. Based on preliminary research and information collection results, the students have difficulty speaking, mainly due to a lack of enthusiasm and the use of learning strategies. Based on the expert’s comments, the developed speaking strategy was generally good and eligible to be used as a strategy for developing the speaking skills of students. So, the use of project-based learning through procedure text that emphasizes practical application and real-life contexts is well suited to optimize language learning outcomes. Overall, the developed strategy proves effective in enhancing students' speaking abilities and creating a conducive learning environment. The study justifies the importance of developing speaking tests through project-based learning due to the significance of speaking skills in language acquisition and the potential of project-based learning to create an engaging and effective learning environment.